Horay Course Review Learning Model: Student Learning Outcomes in Material of Hindu-Buddhist Kingdom in Indonesia - Tasya Lumamena; Leonid Ritiauw; Samuel P. Ritiauw (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Learning the history of the Hindu-Buddhist Kingdoms in Indonesia is often considered boring by elementary school students due to the broad scope of material and conventional teaching methods, which have an impact on low student learning outcomes in class. This study aims to determine the effect of the Course Review Horay (CRH) learning model on student learning outcomes on the material of the Hindu-Buddhist Kingdoms in Indonesia for fifth-grade students at Elementary School 1 Passo. This type of research is an experimental study with a Pretest-Posttest Control Group Design. The study population included all fifth-grade students of Elementary School 1 Passo, totaling 38 students, consisting of class V-a as the experimental group (19 students) and class V-b as the control group (19 students). The research instrument used a learning outcome test in the form of 30 multiple-choice questions that have been tested for validity and reliability. The data analysis technique used an independent sample t-test with a significance level of 0.05. The results showed a Sig. (2-tailed) value of 0.000 <0.05, which indicates a significant difference between the learning outcomes of students in the experimental class and the control class. The average posttest score of the experimental class was 12.053 points higher than that of the control class. Therefore, it can be concluded that the Course Review Horay learning model significantly improves student learning outcomes on the Hindu-Buddhist Kingdoms topic. This research contributes to elementary school teachers' implementation of a fun and interactive cooperative learning model. The CRH model has been proven to create a conducive learning environment to improve students' understanding of narrative history material.